2002
DOI: 10.1038/sj.ejhg.5200830
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the transcobalamin gene: relationship with transcobalamin concentrations and risk for neural tube defects

Abstract: Homocysteine levels are elevated in mothers of neural tube defect (NTD) children, which may be due to a disturbed folate or vitamin B12 metabolism. Vitamin B12 is transported to the tissues by transcobalamin (TC). We previously showed that a low holo-TC/total-TC ratio is a risk factor for NTD, possibly due to an impaired binding of vitamin B12 to TC. The coding region of the TC gene of 12 individuals was analysed for genetic variations responsible for a disturbed vitamin B12 binding. The influence of the genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
6
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 20 publications
11
72
6
2
Order By: Relevance
“…von Castel-Dunwoody et al (2005) reported that the TC C776G polymorphism negatively affected the concentration of the TC-vitamin B12 complex and altered the cellular availability of vitamin B12, thus exacerbating the effects of low vitamin B12 status. There is evidence for an association between TC C776G polymorphism and the increased risk of bearing a child with NTD (Afman et al, 2002;Guéant-Rodriguez et al, 2003). However, no association was observed between the TC C776G polymorphism and the maternal risk of having a child with DS in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…von Castel-Dunwoody et al (2005) reported that the TC C776G polymorphism negatively affected the concentration of the TC-vitamin B12 complex and altered the cellular availability of vitamin B12, thus exacerbating the effects of low vitamin B12 status. There is evidence for an association between TC C776G polymorphism and the increased risk of bearing a child with NTD (Afman et al, 2002;Guéant-Rodriguez et al, 2003). However, no association was observed between the TC C776G polymorphism and the maternal risk of having a child with DS in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Some SNPs in TCN2 change this transporter's affinity for the vitamin. Altered TCN2 affinity for B12 may influence delivery of B12 to tissues, as well as levels of circulating homocysteine, thereby affecting risk of neural tube defects (Afman et al 2002). MTHFR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The malaria parasite requires OCM substrates as cofactors for enzymes essential for growth (Kronenberger et al 2014). The G allele may alter the structure of TCN2 so it has a lower affinity for B12, resulting in its more ready release (Afman et al 2002;Garrod et al 2010).…”
Section: Utilizes Gene Products Frommentioning
confidence: 99%
“…The point estimates from other studies have suggested reduced (34,39,45,47,54), null (31,42), and increased (35,37,41) risks of colorectal cancer for Ala/Ala versus Glu/ Glu. In a meta-analysis of eight previous studies, Ala/Ala versus Glu/Glu was associated with a nonsignificant 17% reduction in colorectal cancer risk, however, statistically significant heterogeneity between studies was observed (11 (59,60). MTR Asp 919 Gly has been inconsistently associated with colorectal cancer risk (31,37,38,43,55,56), with two studies reporting a statistically significant reduced risk for Gly/Gly versus Asp/Asp (38,55 For this analysis, we pooled men and women from two similar studies, the NHS and HPFS, which are both large prospective cohort studies of female and male health professionals that have used similar methods for participant recruitment, blood collection, diet assessment, and follow-up.…”
Section: Resultsmentioning
confidence: 99%